Impact Consumer Attitude Towards Purchase Intention (PI) On Green - Cosmetics in North Kerala - Sabana BACKER; Suresh KOTTAYATH (Communications of International Proceedings, 2022)
Purpose – This research paper tries to find the relationship between consumers' attitude towards green cosmetics and how that can help create purchase intention.  Design/Methodology/Approach –The relationship between consumer attitude and purchase intention (PI) is investigated in this study. Consumers of green cosmetics brands in Kerala's north region are included in the study. To gather information, a structured questionnaire was used. The study involved 387 green consumers from the Kerala districts of Malappuram, Kozhikode and Kasargode. Using Structural Equation Model (SEM) evaluation, the study's hypotheses were tested. Findings –  The test outcomes show that Environmental knowledge directly influences the purchase intention (PI) of consumers. Attitude mediates the association between environment knowledge (EK) and purchase intention of green cosmetic products. Partial mediation through purchase intention exists between the constructs of environment awareness and purchase intention. Environment concern (EC) has significant positive direct impact on the consumers' purchase intention of green cosmetic products. The indirect effect of attitude toward green cosmetic products had a substantial effect on the direct association between environmental concern (EC) and customer purchase intention, according to the mediation analysis. The indirect influence of attitude towards green cosmetic products had no significant impact on the link between subjective norm and customer’s PI. Research implications – This research paper establishes that there is a relationship between purchase intention (PI) and attitude customers have towards environment knowledge (EK), environmental concern, online availability, subjective norms, and greenwashing. The study provides empirical evidence so that companies can bring in more business by influencing the consumers' attitudes. Practical implications – The research can give empirical evidence to producers of green cosmetic consumers on variables such as attitude, environmental concern, online purchase habit and purchase intention. The results can help green cosmetic companies to form strategies to build a strong market. Originality/value – The study explores the influence of consumer attitude towards green cosmetics on the formation of purchase intention among the users of green cosmetics and adds value to the academic areas of consumer attitude and purchase behavior.
Keywords: Purchase Intention; Attitude; Green cosmetics; Environmental concern; Purchase intention